A Review of Golden Days of Deep Learning Process - Jyothi, K; Sunitha, K (International Journal of Computer Sciences and Engineering, 2025)
The finish of Moore’s law and Dennard scaling has prompted the finish of fast enhancement all in all reason program execution. Machine learning (ML), and specifically profound learning is an appealing option for designers to investigate. It has as of late altered vision, discourse, dialect understanding, and numerous different fields, and it guarantees to help with the fabulous difficulties confronting our general public. The calculation at its center is low-accuracy straight variable based math. Accordingly, ML is both sufficiently wide to apply to numerous areas and sufficiently tight to profit by space explicit models, for example, Googles Tensor Processing Unit (TPU). In addition, the development sought after for ML registering surpasses Moore’s law at its pinnacle, similarly as it is blurring. Consequently, ML specialists and PC modelers must cooperate to plan the registering frameworks required to convey the capability of ML. This article offers inspiration, proposals, and alerts to PC draftsmen on the best way to best add to the ML insurgency.